Number of familiarisation sessions required for an isokinetic knee strength assessment in female varsity athletes - Chan Jerusha Poe Yin, Yusof Ashril, Selvarajah Victor Selvanayagam, (Universiti Pendidikan Sultan Idris, 2016)
Number of familiarisation sessions required for an isokinetic knee strength assessment in female varsity athletes by Chan Jerusha Poe Yin, Yusof Ashril, Selvarajah Victor Selvanayagam,